Pemikiran Ibnu Rusyd tentang Pendidikan dan Relevansinya dengan Dunia Kontemporer - Amaanulloh Abror (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2021)
The purpose of education according to Ibn Rushd is to provide correct knowledge so that it can be implemented into the right actions as well. For this reason, educational materials and learning methods must be adapted to the readiness of human thinking as the subject of education. Of course, the level of readiness to think of ordinary people is different from that of educated people. This study is to determine the biographical background, life, and thoughts of Ibn Rushd about education, then to find the relevance of Ibn Rushd's educational thoughts with Islamic education in this modern era. The method used in the preparation of this paper is the library method. The researcher collected data sources through text literature, both books, journals, and articles that are relevant to this discussion. The results showed that Ibn Rushd was a philosopher, expert in fiqh, medicine and also a legal expert. Ibn Rushd has ideas and thoughts related to education, that education is practical which must be assisted through a theoretically appropriate model so that practical implementation is always in accordance with its theoretical implementation which aims to provide correct knowledge so that it can implement it into the right action as well. Ibn Rushd's thoughts on organized education in goals, curriculum, learning methods and teachers or educators are factors of determinant elements in education. Therefore, Ibnu Rushd's thoughts can be used as important references in the progress of the world of Education.